Digitalization Development as Factor Causing Changes in Taxation Administration - V. I. Bratcev (Plekhanov Russian University of Economics, 2021)
The article demonstrates the key lines in digital transformation of Russian taxation bodies aimed at ensuring the development of tax regulating methods. Managing changes in the field of digital economy requires designing and adopting regulatory decisions, which could eliminate barriers and create favorable conditions for the development of this field and cut risks connected with broad application of new technologies. In order to perform their principle functions, including those providing a high level of cash receipts to the budget system of the Russian Federation in conditions of economy digitalization tax bodies today shall develop their own digital platform, around which the ecosystem for taxpayers will be formed. The authors researched the impact of the economy digitalization process on transforming the approach to tax regulation, the focus of which is turning the system of tax bodies into the adaptive digital platform. Key indicators of the digital technology sector of the Russian Federation were studied and opportunities of the sector’s impact on tax regulation were identified. On this basis the authors showed the necessity to upgrade software products of tax bodies, which are used within the frames of tax administration. The interconnection of forms and lines of digitalization with processes of institutional changes in tax regulation was described. Among key findings of the research it is necessary to highlight substantiation of the tax system transformation under the influence of speeding-up development of digital technologies and elaboration of practical recommendations aimed at upgrading the tax administration mechanism by introducing automated multifunctional consolidating analytical tools.